Juner New Materials : on the road to IPO - Zhao, Ziqian, (SAGE knowledge. Cases., 2016)
Juner had been operating in China's modified plastics material industry for fifteen years and had exhibited strong growth and profitability. However, in 2010, the company's founder and chairman, Xiaomin Chen, began to instigate ambitious future growth plans. This book details Juner's strategies.